Effects of irrigation on nematode communities in wheat field - LI Xiu-xia; WU Hai-yan; SHI Li-bo (浙江大学学报. 农业与生命科学版)
Effects of irrigation on nematode community in wheat field soil ecosystem were studied, the soil samples from different irrigation fields were collected, and the nematodes were extracted through sucrose-centrifuge and were identified to the genus level with the aid of microscope. A total of 16073 soil nematode individuals were captured and fell into 25 families and 35 genera, including four trophic groups, i.e. plant-parasites (PP), fungivores (F), bacterivores (B) and omnivore-predators (OP). Bacterivores was the dominant trophic group that account for 56.1% of the total individuals. Cephalobus, Aphelenchus and Tylenchorhynchus were the dominant genera. The total of nematodes and bacterivores in T1 treatment were more than those of the other treatments, and showed significant difference (P<0.05). Irrigation had significant effect on vertical distribution of soil nematode, the number of nematode at 0-10 cm soil depth in T1 treatment was more than that of other treatments (P< 0.01). Diversity index of vertical distribution of soil nematode community was influenced by different irrigation treatments. In conclusion, jointing stage water (T1) can promote multiplication of bacterivores, improve soil health, and be benefit to sustaining development of soil resource.